Role of neutrophil to lymphocyte ratio in predicting severity of acute appendicitis - Neupane, Jeevan; Aacharya, Ramesh Prasad; Gupta, Sanjay Kumar; Mishra, Abhishek; Mahat, Pradeep; KC, Bipana (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Acute Appendicitis is a common and urgent surgical illness with protean manifestations, generous overlap with other clinical syndromes and significant morbidity which increases with diagnostic delay. Scoring tools have been criticized for lack of sensitivity and specificity and they don’t predict the severity of illness. Our aim was to assess the association between neutrophil-tolymphocyte ratio and its effectiveness as a tool for predicting the severity of acute appendicitis.Method: A prospective observational study was conducted at a tertiary care center in adults presenting to the emergency department diagnosed as acute appendicitis from December 15, 2022 to December 16, 2023. The study involved the calculation of Neutrophil to lymphocyte ratio for the enrolled patients using statistical analyses The calculated value can serve as a marker of severity of acute appendicitis.Result: Among 100 patients included in the study, males predominated- 54 (54%). Majority 58 (58%) had simple appendicitis. The sensitivity, specificity, positive predictive value and negative predictive value were 90.5%, 91.4%, 44.19% and 99.2% respectively. Similarly the area under the ROC curve and cutoff point of neutrophil to lymphocyte ratio for differentiating complicated and uncomplicated appendicitis were 0.945, and 7.54 respectively. A significant association was seen between neutrophil to lymphocyte ratio and the occurrence of complications (p-value < 0.001).Conclusion: The Neutrophil-to-Lymphocyte Ratio (NLR) can serve as a predictor for severity of acute appendicitis. This has significant implications for prioritizing surgical cases and monitoring patients who are treated conservatively.